Figurative Expressions in the Short Story of âSepotong Tubuhâ and their Translation into English - Yulianti, Ni Ketut Dewi; Yadnya, Ida Bagus Putra (International Research Journal of Management, IT & Social Sciences, 2016)
This paper is a descriptive translation study focusing on the types of figurative expressions used in the short story of âSepotong Tubuhâ and how they are translated into English in the short story of âBodyâ. The study departs from a paradigm that looks upon the translation of the short story as a product and tries to analyze the theme of the short story in both the source and the target language texts since theme is the motivating force of any literary works. Understanding the theme will lead to the understanding of the figurative expressions used in the short story as the use of figurative expressions is motivated by the theme of the short story. Theoretically, the study is an eclectic one based on the theories concerning strategies for translating figurative expression proposed by Larson and the theory of translation proposed by Nida and Taber. This paper is expected in the first place to provide some insights for those who are interested in translation studies especially figurative expressions and in the second place to be beneficial for translation practices.